Fermented Beverage Based on Lupines (Lupinus luteus) Using Water Kefir - Catharina Weis, Claudia Moreira Santa; Techi Diniz, Luan Gabriel; Andrade, Gessica Suiany; Monteiro, Luciane Mendes; Manfron, Jane; Camargo, Aline Frumi; Kubeneck, Simone; Klein, Gabriel Henrique; Romani, Larissa Capeletti; Longo, Vitoria Dassoler; Nerling, Julia Pieper; Tormen, Luciano; et al. (Food Science and Engineering, 2024)
This research aimed to elaborate and characterize a fermented lupine vegan drink from water kefir grains. Firstly, the standard protocols were carried out to extract and identify alkaloids in lupine. The second stage consisted of elaborating the water-soluble lupine vegetable extract (WLVE), and the effect of sucrose, inulin, and xanthan gum concentration on the extract was evaluated. The formulations were characterized for cell growth of kefir grains, beverage yield, soluble solids, and lactic acid. In the third step, the optimized drink (fermented and non-fermented) was characterized for moisture content, ash, total lipids, crude protein, and determination of total carbohydrates. The elaboration and characterization of a fermented vegan drink from water kefir grains using lupine was conducted. The optimized fermented drink was the formulation given by the central point. The lupine seed characterization revealed a high protein content, and the optimized beverage characterization showed a considerable carbohydrate content. The optimized drink has enzymatic activity with an emphasis on lipases. The drink's development as a new product using water-soluble lupine plant extract brought an exciting application for this legume and an additional food option for vegan consumers or consumers with dietary restrictions related to dairy products.